Efficacy and safety of anlotinib monotherapy for advanced hepatocellular carcinoma and clinical role of α-fetoprotein - Jianping Chang; Bowen Xu; Zhiyu Li; Zhicheng Wei; Xu Che; Jianqiang Cai; Yanjiang Yin; Xinyu Bi (Scientific Reports)
Abstract Anlotinib, a novel multi-targeting tyrosine kinase inhibitor (TKI), has been investigated in a variety of malignant tumors. This retrospective study was designed to investigate the efficacy and safety of anlotinib as first- or second-line therapy for advanced or metastatic hepatocellular carcinoma (HCC), and to identify early predictors for disease control. This multicenter retrospective study included 158 patients with advanced HCC. 54 patients received anlotinib and 104 patients received sorafenib. Progression-free survival (PFS), overall survival (OS), and treatment response were compared. Subgroup analyses and biomarker evaluations were also conducted. Anlotinib demonstrated significantly improved OS compared with sorafenib in the second-line setting (13.0 vs. 11.0 months; P = 0.010), although no significant differences in ORR, DCR, or PFS were observed. Subgroup analyses revealed that patients with AFP ≥ 400 ng/mL or HBV infection derived greater OS benefit from anlotinib. AFP response—defined as a ≥ 25% reduction at 4 weeks—was identified as an independent early predictor of disease control, and this association held true in both high-AFP and low-AFP subgroups. Anlotinib showed encouraging survival benefits and acceptable safety in advanced HCC, particularly in the second-line setting. AFP response may serve as an early biomarker for treatment efficacy. These findings warrant validation in future prospective studies.